Application of the GUT Method (Gravity, Urgency, and Trend) in Damage Maps of the Duarte Coelho and Maurício de Nassau Bridges with Software Assistance - Albuquerque , Everson Silva de; Teixeira, Igor Albuquerque da Rosa; Barros , Eduardo Oliveira; Nascimento , Carlos Fernando Gomes do; Monteiro , Eliana Cristina Barreto (Technical and Scientific Journal Green Cities, 2025)
Bridges play a crucial role in the logistics of the Metropolitan Region of Recife (RMR), directly impacting the economy and urban development. Given their importance, monitoring their condition is essential to ensure safety and functionality. This study investigated the pathological manifestations in the Duarte Coelho and Maurício de Nassau Bridges in Recife/PE, aiming to create damage maps and systematically review the identified issues. Visual inspections were conducted using identification forms, recording the damages through photographs and Unmanned Aerial Vehicle (UAV) images. The damage maps, developed in AutoCAD, highlighted problems such as mold, moisture stains, efflorescence, cracks, concrete spalling, and reinforcement corrosion. The analysis indicated that most of these issues could be prevented with routine maintenance. The bridges were found to be in moderate condition, with corrosion and cracks being the highest-priority anomalies, classified using the GUT method with the assistance of software developed in Visual Studio Code. The study emphasizes the need for immediate repairs and the implementation of a regular maintenance plan, ensuring the preservation of these structures and their significance to the city.
Keywords: Bridges; Pathological manifestations; Damage map; Durability